KESEIMBANGAN PERAN GENDER PERSPEKTIF AL-QUR’AN - Inda, Marlinda; Nurfiati, Nurfiati (TAFASIR: Journal of Quranic Studies, 2024)
This research examines the Qur'anic perspective on gender role balance between men and women. This study aims to analyze Qur'anic verses that discuss gender relations and reveal how this holy book provides a comprehensive view of equality and balance of roles between the sexes. Through a thematic interpretation approach and contextual analysis, this research demonstrates that the Qur'an teaches principles of gender equality in various aspects of life, such as spiritual, social, educational, and economic. The findings reveal that the Qur'an does not discriminate against any particular gender, but rather emphasizes complementary roles and responsibilities between men and women. A proper understanding of the concept of gender balance in the Qur'an can provide a foundation for creating a more just and harmonious society..